Divergent Intramedullary Nailing (DIN): A Modified Intramedullary Nailing Technique to Treat Paediatric Distal Tibial Fractures. Issue 10 (November 2019) - Harly, Edouard; Angelliaume, Audrey; Lalioui, Abdelfetah; Pfirrmann, Clémence; Harper, Luke; Lefèvre, Yan
Abstract : Introduction: Elastic stable intramedullary nailing (ESIN) allows for efficient reduction and stabilization of fractures of the tibial shaft in children and adolescents. However, for fractures of the distal third of the tibia, traditional ESIN could be inappropriate, thus compromising the stability and the healing of the fracture. The aim of this study was to present and to assess a new technique of modified ESIN to treat fracture of the distal third of the tibia, called divergent intramedullary nailing (DIN). Methods: We performed a retrospective monocentric study. All patients less than 16 years old, managed in our pediatric orthopaedics department, and operated upon according to the DIN technique for a displaced and/or unstable fracture of the distal third of the tibia were included. Demographic and surgical data were collected. X-rays were performed preoperatively, postoperatively, at 6 weeks, and every 6 months. The surgical technique starts as does the classic ESIN. However, nails are not curved, so that they cross only once at the proximal part of the tibia; they are divergent and supported by the medial and lateral distal part of the tibial shaft. This allows for reduction and stabilization of the fracture. Results: A total of 13 patients were included, with a mean age of 10 years and a mean follow-up of 32 months. The size of the nail varied between 2.5 and 4 mm. The mean surgical time was 54 minutes. The DIN technique provided a satisfying reduction (coronal and sagittal angulation <3 degrees) for the 13 fractures. In addition, there was no secondary displacement at 6 weeks. All patients were healed at 6 months, with no clinical torsion or axis malalignment. Conclusions: The current study confirms the feasibility and the efficiency of the DIN method to treat fracture of the distal third of the tibia.